Heaven official's blessing, manhua. Volume 5 - Moxiangtongxiu (Aloha Comics, 2025)
"As a fierce sandstorm rages outside, our heroes seek refuge in a mysterious cave, only to discover a merchant caravan huddled there, waiting out the storm. But the cave holds a darker secret -- it's the ancient tomb of a legendary general who fought in this very spot two centuries ago, around the same time Xie Lian was scavenging nearby...The merchants believe Banyue Pass is safe, with a skilled guide leading the way. But fate has other plans: a sudden attack by deadly scorpion-snakes leaves a merchant and the crown prince poisoned. The only hope for survival lies in the rare shanyue herb, hidden within the ruins of a long-lost city. Will our heroes find it in time? The adventure just took a deadly turn!" --